Soil Microbial Community, Soil Quality, and Productivity along a Chronosequence of Larix principis-rupprechtii Forests - Jing Zhang; Qiang Liu; Dongzhi Wang; Zhidong Zhang (Plants, 2023)
Elucidating the correlation between soil microbial communities and forest productivity is the focus of research in the field of forest ecology. Nonetheless, the relationship between stand age, soil quality, soil microorganisms, and their combined influence on productivity is still unclear. In this study, five development stages (14, 25, 31, 39, and >80 years) of larch (Larix principis-rupprechtii) forests were investigated in Inner Mongolia and Shanxi provinces of China. We evaluated soil quality using the Integrated Soil Quality Index (SQI) and analyzed changes in bacterial and fungal communities using high-throughput sequencing. Regression models were also established to examine the impacts of stand age, microbial diversity, and SQI on productivity. The findings revealed an ascending trend in soil organic matter (SOM), total nitrogen (TN), total phosphorus (TP), available potassium (AK), and SQI in 14, 25, 31, and 39-year-old stands. The abundance of oligotrophic bacteria Acidobacteria exhibited a gradual decline with increasing forest age, whereas copiotroph bacteria Proteobacteria displayed a progressive increase. Stands older than 80 years exhibited a higher abundance of both the saprophytic fungus Ascomycota and mycorrhizal fungus Basidiomycota. Forest age had a significant impact on microbial diversity, particularly in terms of bacterial diversity, impacting both α and β diversity. The soil bacterial community structure was influenced by AK, SOM, TN, TP, and pH. Conversely, the fungal community structure was regulated by crucial factors including SOM, TN, TP, TK, AK, and pH. Fungal diversity demonstrated a significant and positive correlation with the basal area increment (BAI) of larch. Furthermore, microbial diversity accounted for 23.6% of the variation in BAI. In summary, the findings implied a robust association between microbial composition, diversity, and soil chemical properties throughout the chronosequence of larch forests. These factors collectively played a crucial role in influencing the productivity of larch forest.